Antioxidant Poperties and Medicinal Uses of Some Crataegus Spp. (Hawthorn) Including C. Meyeri and C. Pontica - Dolatkhani, Parisima; Jameie, Rashid (Current Nutrition & Food Science, 2015)
Hawthorn (Crataegus spp.) is a well known medicinal plant, commonly used for its heart tonic properties. When it comes to herbal treatment of the heart ailments, Hawthorn is always at the peak of the herbalists' crop. Scientific researches have repeatedly verified this heart-friendly herb's reliability and non-toxicity. The cardiac tonic properties of Hawthorn are attributed to its phenolic and flavonoid contents distributed throughout the plant parts and its by-products. This paper goes over antioxidant properties and medicinal uses of some Crataegus spp. including C. meyeri and C. pontica having relatively high antioxidant and antiradical activities. The advantages of using natural remedies over their synthetic equivalents are discussed, emphasizing on the necessity of thorough investigations on many Crataegus species not yet studied.
Keywords: cardiac tonics